1985
DOI: 10.1159/000199214
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Secretin and Motilin Responses to Graded Duodenal Acidification in Anaesthetised Pigs

Abstract: The effects of graded duodenal acidification on plasma concentration of immunoreactive secretin, and motilin in portal vein (PV) and carotid artery (CA) were investigated in 6 anaesthetised pigs in which the proximal duodenum was excluded and sequentially irrigated with isotonic saline (pH 7.0) and with hydrochloric acid (HC1) delivered at successive rates of 2, 8 and 40 mM H+/40 min(pH of 2.8, 1.9 and 1.0, respectively) under a constant flow of 10 ml/min. The release of secretin was first observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Our data clearly indicate that the presence of bile in the duodenum may cause a motilin release. This indicates that emptying of the gallbladder may play an important role in the motilin release ob served in relation to ingestion of a meal [30,40], Acidification of the duodenum as a stimulating factor for motilin release has been reported by several groups, Motilin Release from the Pig Duodenum for instance Bloom et al [33] in man, Cuberet al [41] in pig, and our results support this view. Thus, emptying of low pH chyme from the stomach into the duodenum may also be an important factor for the motilin release ob served in relation to a meal.…”
Section: Perfusion Experimentssupporting
confidence: 86%
“…Our data clearly indicate that the presence of bile in the duodenum may cause a motilin release. This indicates that emptying of the gallbladder may play an important role in the motilin release ob served in relation to ingestion of a meal [30,40], Acidification of the duodenum as a stimulating factor for motilin release has been reported by several groups, Motilin Release from the Pig Duodenum for instance Bloom et al [33] in man, Cuberet al [41] in pig, and our results support this view. Thus, emptying of low pH chyme from the stomach into the duodenum may also be an important factor for the motilin release ob served in relation to a meal.…”
Section: Perfusion Experimentssupporting
confidence: 86%
“…The acidification of the proximal duodenum was previously shown to induce the release of secretin and motilin in anaesthetised pigs [43]. A temporal relationship was evidenced in conscious fasting pigs between the successive phases of MMC and the cyclical variation of plasma motilin, pancreatic polypeptide, and gastrin, but not somatostatin [42,44].…”
Section: Motor and Secretory Coordination In The Gastroduodenal Areamentioning
confidence: 84%
“…Later on, several regulatory peptides such as motilin, cholecystokinin, secretin, pancreatic polypeptide, neurotensin, etc., were also shown to play an important role in the control of gastrointestinal motility [42,43] and digestive secretions [45,46,85,86,120]. Moreover, Rérat et al [158] showed that an increase in the level of proteins in the diet induced large changes in the hormonal purified proteins, e.g.…”
Section: Integrative Approaches: Neurohumoral Regulations and Adaptatmentioning
confidence: 99%
“…Cyclical variations in the plasma levels of motilin (Cuber, Laplace and Chayvialle, 1984), cholecystokinin (Cuber et al, 1986a), gastrin and pancreatic polypeptide (Cuber et al, 1986b) with a periodicity closely related to that of the MMC were recently described in the pig. Results obtained in pigs also suggest that the acidification may lead to a growing release of various peptides such as secretin (Cuber et al, 1985). The occurrence of a pH close to neutrality during early RSA may interrupt this release and could account for the rapid decrease in biliary and pancreatic flow rates.…”
Section: Introductionmentioning
confidence: 90%